Joint Evaluation of Employment Guarantee Scheme of Maharashtra 1. Field Report 2. State Level Information 3. Current Status - Planning Commission (Planning Commission, 1977)
As part of the Joint Evaluation of the Employment Guarantee Scheme being conducted by the Programme Evaluation Organisation (PEO) and the Evaluation Division of the Directorate of Economics and Statistics (DES) of Maharashtra. Talukas were taken up for a quick survey, in the first instance. The objectives of the Joint Evaluation, which is to continue for two years are fairly comprehensive. The present effort was mainly intended to gain first-hand experience of the field situation so that the further study could be suitably organised. The availability of detailed information was a major consideration for initiating the present work in Sholapur district, which was also perhaps the district recording the highest expenditure during scarcity years and also under EGS in 1974-75.
Programme Evaluation Organisation, Planning Commission, Government of India